Peningkatan Capaian Raport Mutu melalui Pelatihan Pembelajaran Interaktif Berpusat pada Siswa - Muhtarom, Muhtarom; Sumarno, Sumarno; Sugiyanti, Sugiyanti; Nuvitalia, Dwi (Pelita: Jurnal Pengabdian kepada Masyarakat, 2025)
Community service aims to 1) improve teacher competence through training, 2) improve understanding of interactive learning strategies that are centered on students, 3) provide experience in strategies for managing behavior to create a safe and comfortable environment for students, 4) train the use of information technology for learning. This is a response to efforts to improve the achievement of education quality reports which based on analysis show the root of the problem of declining learning quality due to the implementation of interactive and innovative learning methods. The results of the activity show that the training provides provisions for interactive learning teachers, provides provisions for creating learning practices that facilitate managing inclusive and non-discriminatory behavior, motivates students, and helps students build new knowledge, realizing student-centered education.